2020
DOI: 10.4102/sajesbm.v12i1.320
|View full text |Cite
|
Sign up to set email alerts
|

Impact of venture capital financing on small- and medium-sized enterprises’ performance in Uganda

Abstract: Background: Small- and medium-sized enterprises (SMEs) in Africa and Uganda suffer from lack of finance for their survival and growth. This liquidity emergency motivated start-ups struggling to find alternative financing sources different from conventional bank lending. Venture capital financing evolved as viable financial mechanisms to revive SMEs’ performance.Aim: This article analysed the impact of venture capital financing on SMEs’ performance in Uganda. This is the first empirical study that related and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 32 publications
(37 reference statements)
1
14
0
Order By: Relevance
“…Endogenous factors have not been given ample attention in small business research, even though in some countries they have been found to complement exogenous factors effectively. According to Blume and Sargent (2015), a holistic entrepreneurial activity is that which successfully harnesses both exogenous and endogenous components in its framework, although there is a strong belief that a significant component of SMMEs' failure is attributable to constraints from the exogenous environment, especially finance (Agbenyegah 2013;Agwa-Ejon & Mbohwa 2015;Asongu & Odhiambo 2019;Cant & Wiid 2013;Chimucheka & Rungani 2011;Kato & Tsoka 2020;Moos & Sambo 2018). It becomes particularly worrisome when the majority of SMMEs with access to various forms of exogenous support still fail (Sustainable Development Consortium 2007;Madichie, Mpiti & Rambe 2019;Malebana 2017;Ramukumbasup et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Endogenous factors have not been given ample attention in small business research, even though in some countries they have been found to complement exogenous factors effectively. According to Blume and Sargent (2015), a holistic entrepreneurial activity is that which successfully harnesses both exogenous and endogenous components in its framework, although there is a strong belief that a significant component of SMMEs' failure is attributable to constraints from the exogenous environment, especially finance (Agbenyegah 2013;Agwa-Ejon & Mbohwa 2015;Asongu & Odhiambo 2019;Cant & Wiid 2013;Chimucheka & Rungani 2011;Kato & Tsoka 2020;Moos & Sambo 2018). It becomes particularly worrisome when the majority of SMMEs with access to various forms of exogenous support still fail (Sustainable Development Consortium 2007;Madichie, Mpiti & Rambe 2019;Malebana 2017;Ramukumbasup et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a quick analysis of the VC markets of European Union (EU) countries reveals that from 2007 to 2019 EU governmental agencies provided €16.4 billion of VC funds to EU countries (Invest Europe, 2020; Kallay & Jaki 2020). Nonetheless, little is known about government VC funding in African countries because the contributions of their regimes to the VC industry in Africa is minimal (Deventer & Mlambo, 2008;Deloitte & SAVCA, 2009;Agyeman, 2010;Shanthi et al, 2018: Mboto et al, 2018Kato & Tsoka, 2020;Maurizio, 2020). This paper, therefore, attempts to discover why Africa's VC market has been under-exploited; evidence from Uganda is utilised to facilitate this discovery.…”
Section: Introductionmentioning
confidence: 99%
“…This paper, therefore, attempts to discover why Africa's VC market has been under-exploited; evidence from Uganda is utilised to facilitate this discovery. Despite the pitfalls observed in the VC industry in Africa, topical literature underwrites VC as the primary funding instrument for early-stage entrepreneurial firms (Baldock, 2016;Biney, 2018;Rosa et al, 2019;Thies et al, 2019;Kato & Tsoka, 2020;Gompers et al, 2020;Lerner & Nanda, 2020;Gaies et al, 2021). Besides, scholars disclose that the surpassing growth of the United States (US) VC markets can be squarely attributed to far-reaching government patronage provided directly by government VC funding (GVCF) and the enactment of supportive regulatory reforms (Gompers & Lerner, 2001;Lerner 2010;Deloitte & NVCA, Owen et al, 2019;Lerner, 2020: Gompers et al, 2020NVCA, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations